Challenges Presented by Pilgrimage Sites and their Impact on Ecology of Protected areas: A Case Study of Ranthambhore Tiger Reserve, Rajasthan - Dhakad, Meenu; Khandal, Dharmendra; Paranjpe, Dhanashree A.; Dhar, Ishan; Saini, Mukesh; Sahu, Y. K. (Indian Forester, 2020)
The traditional pilgrimages to religious sites are evolving into large scale religious tourism in many protected areas across India. A growing influx of visitors leading to infrastructural development of these sites within protected areas has potential to immensely damage the natural ecological balance. There are significant changes in the scale and frequency of visits to religious sites over past few decades creating an undue anthropogenic pressure on the ecology of protected areas. The present study tried to estimate the impact of religious tourism on the local ecology inside Ranthambhore Tiger Reserve (RTR), India. Through direct field mapping and interview based surveys in RTR, 352 religious sites were documented. Out of 215 grids of 2x2 km laid down using GIS mapping, 135 (62.79%) grids had religious sites and the accompanying pilgrims in the critical tiger habitat. Disturbance indices for a subsample of randomly selected 42 religious sites were calculated considering ten potential disturbance factors. There was a positive correlation between number of annual visitors to the selected sites (N=42) and the amount of garbage found at the sites. Authors have suggested some measures to reduce the impact of religious tourism on local ecology.